Reconfigurable Anisotropic Coatings via Magnetic Field‐Directed Assembly and Translocation of Locking Magnetic Chains. (22nd April 2014) - Tokarev, Alexander; Gu, Yu; Zakharchenko, Andrey; Trotsenko, Oleksandr; Luzinov, Igor; Kornev, Konstantin G.; Minko, Sergiy
<x xml:space="preserve">Abstract</x> A method for the generation of remotely reconfigurable anisotropic coatings is developed. To form these coatings, locking magnetic nanoparticles (LMNPs) made of a superparamagnetic core and a two‐component polymer shell are employed. Two different polymers form phase‐separated coaxial shells. The outer shell provides repulsive interactions between the LMNPs while the inner shell exerts attractive forces between the particles. Applying a non‐uniform magnetic field, one gathers the particles together, pushing them to come in contact when the internal shells could effectively hold the particles together. When the magnetic field is turned off, the particles remain locked due to these strong interactions between internal shells. The shells are thus made stimuli‐responsive, so this locking can be made reversible and the chains can be disintegrated on demand. In a non‐uniform magnetic field, the assembled chains translocate, bind to the solid substrate and form anisotropic coatings with a "locked" anisotropic structure. The coatings can be constructed, aligned, realigned, degraded, and generated again on demand by changing the magnetic field and particle environment. The mechanism of the coating formation is explained using experimental observations and a theoretical model.